Pemetaan Potensi Desa di Gampong Pasie Mesjid Menuju Gampong Syari’at - Sukri; Muflihatul Fauza; Ramli; Muhammad Iqbal; Asnidar; Nelva Sofia; Emarlina; Satra Ika Dinata (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2023)
Gampong Pasie Mesjid, Meureubo District, West Aceh Regency which is the target village for the lecturers and students of STAIN Teungku Dirundeng Meulaboh. Keuik Rustam as the head of the gampong wants this gampong to have progress in the economic field and become an Islamic village based on Islamic shari'ah in accordance with the vision of the West Aceh District Government. For this reason, community service activities are carried out in the form of mapping village potential and religious potential. This activity then produced several findings related to economic development that could be implemented based on local resources and strategies for strengthening religion through early childhood education, women's recitation and Friday sermons.